Pengaruh Gaya Kepemimpinan, Komunikasi dan Kompensasi terhadap Kinerja Karyawan PT Sinar Sejahtera Jaya Tjipta Group Kota Metro - Andika, Romi; Septiana, Nani (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study is to find empirical evidence of the influence of organizational commitment and human resource competence on the use of information technology in the regional work units (SKPD) of the city of metro. The study was conducted on a regional work unit (SKPD) of the city of metro with a sample of 40 respondents. Sampling using a purposive sampling technique, and data collection techniques using questionnaires. Data analysis techniques using Pearson product moment correlation analysis and multiple regression using the SPSS application. The results of the study concluded: (1) Organizational commitment influences the quality of the financial statements of the metro city government; (2) Human resource competence has an influence on the quality of the financial statements of the metro city government; (3) The use of information technology has an effect on the quality of the financial statements of the metro city government;